AUDIT ENERGI DI MESIN KERTAS - Dina, Sari Farah; Susanto, Herri (JURNAL SELULOSA, 2006)
Energy audit were conducted in five paper mills, namely: A B,C, D and E with different paper machine and process conditions. Mill A is relatively old  and small with a capacity of 160 ton/day of print paper. The steam consumption of mill A was 2.01 ton/ton product, which was higher than that of mill B (1.41 ton/ton). This large different steam consumption might be due to a high water content of paper entering the paper machine (up to 62.83%). A highest steam consumption up to 3.76 ton/ton product was found in Mill E having a small capacity of 38 ton/day. Besides the fact that paper machine in Mill E was old and had no hood, type of product (grammage of 284 g/m2) might also contribute to this high steam consumption. Two other mills producing corrugated paper (mills C and D: with a grammage of 115 and 125 g/m2 respectively) had steam consumptions of about 1.9 ton/ton product, within the range of 1.8 – 2.2 ton/ton reported in literature.Mill B with a capacity of 984 ton/day was the largest mill in this study. Current steam consumption of mill B of about 1.41 ton/ton of product was the lowest among the other four mills. This mill has implemented an energy conservation program. By means of reducing water content in paper entering the drying machine from 54% to 51%, the steam consumption was reduced from 1611 to 1440 ton/day. From a simple mass and heat balance, increasing water content in paper leaving paper machine from the present value of 4% to the allowable one of 5% might also give another saving of steam.  INTISARIAudit energi telah dilakukan pada lima pabrik kertas, dinamai A, B, C, D dan E, dengan berbagai kapasitas dan kondisi proses. Pabrik A memiliki kapasitas kecil, hanya 180 ton/hari dan sudah tua. Konsumsi steam pabrik ini sekitar 2,01 ton/ton kertas, jauh lebih tinggi daripada pabrik B (1,41 ton/ton). Perbedaan mencolok ini salah satunya disebabkan perbedaan kadar air dalam kertas saat masuk mesin kertas (kadar air sampai 62,83% di pabrik A). Konsumsi steam terbesar ditemui di pabrik E (3,76 ton/ton) yang memiliki kapasitas produksi kertas 38 ton/hari. Pabrik E yang sudah tua ini memproduksi kertas tebal (gramatur 284 g/m2) dan mesin kertasnya tidak dilengkapi dengan hood. Dua pabrik kertas lainnya memproduksi corrugated-paper: pabrik C dengan gramatur 115 dan pebrik D 125 g/m2. Konsumsi steam kedua pabrik ini sekitar 1,9 ton/jam, masih dalam rentang konsumsi steam 1,8 – 2,2 ton/ton kertas yang dilaporkan di beberapa pustaka. Pabrik B merupakan pabrik terbesar dengan kapasitas 984 ton/hari, telah menerapkan program-program penghematan energi. Konsumsi steam pabrik ini adalah 1,41 ton/ton produk, paling rendah di antara kelima pabrik yang ditinjau. Dengan menurunkan kadar air pada kertas sebelum masuk mesin pengering, pabrik ini dapat menghemat pemakaian steam dari 1611 menjadi 1440 ton/hari. Disamping itu perhitungan neraca massa dan energi menunjukkan masih adanya penghematan konsumsi steam jika kadar air dalam kertas keluar mesin pengering dapat dinaikkan dari kebiasaan 4% menjadi yang diijinkan 5%.